WHEN THE CLIMATE REWRITES THE FORECAST (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
For much of human history, weather has been regarded as one of nature’s greatest uncertainties. Storms, droughts, floods, and heat waves have always occurred, shaping civilizations, influencing agriculture, and challenging societies. Today, however, scientists are observing a profound transformation in the Earth’s climate system. Weather events that were once considered statistically rare are becoming increasingly frequent and more intense. This shift has prompted extensive scientific investigation into one of the defining questions of the twenty-first century: how is climate change influencing extreme weather?
Keywords: The scientific consensus is built upon decades of research conducted by climatologists, meteorologists, oceanographers, and environmental scientists worldwide. Modern climate science combines satellite observations, atmospheric monitoring, historical weather records, oceanographic data, and sophisticated computer simulations to understand the complex interactions within Earth’s climate system. Together, these studies provide compelling evidence that human activities have significantly altered the composition of the atmosphere, accelerating global warming and increasing the probability of many extreme weather events.